Implementation of Marketing Mix Strategy (4P) to Increase Sales of NOA Everyday Products (Lembang Branch) - Mitha Fania Listiani; Muhammad Adam Sudaryanto (CV. Civiliza Publishing, 2026)
This study aims to analyze the application of the 4P marketing mix strategy which includes products, prices, places, and promotions at NOA Everyday Lembang Branch and its contribution to increasing sales. NOA Everyday is a local women's fashion brand from Bandung that carries the concept of simple, comfortable, and stylish to meet daily clothing needs. This study uses a qualitative descriptive method with data collection techniques through observation, semi-structured interviews, and documentation. The research informants were selected using purposive sampling, namely employees who are directly involved in marketing and store operations. The results of the study show that the 4P marketing mix strategy has been implemented in an integrated manner and has made a positive contribution to increasing sales. From the product aspect, NOA Everyday offers quality clothing with designs that follow market trends. From the price aspect, the company implements a competitive pricing strategy according to the middle market segment. From the aspect of place, strategic store location and presence on digital platforms expand the reach of consumers. From the aspect of promotion, the use of social media, e-commerce, and collaboration with influencers has been proven to increase brand awareness and sales. This study concludes that the optimal implementation of the 4P marketing mix strategy contributes positively to increasing sales and competitiveness of NOA Everyday Lembang Branch.